MODAL SOSIAL PEREMPUAN PESISIR DAN UPAYA PENCEGAHAN HIV/AIDS DI KABUPATEN JEMBER - Rina Rohmawati; Deditiani Tri Indrianti (Jurnal CULTURE (Culture, Language, and Literature Review), 2018)
This study aims to build the resilience of coastal women from the threat of HIV / AIDS spreading by using the social capital base as the media. Social capital has very important role forthe life of coastal women. Social capital is built by trust among individuals who interacts oneanother. Mutual trust is established for short time and requires tortuous social processes. The typesof social capital can be understood as follows: first, social networks, voluntary private networks;second, civic engagement and participation and the use of civil networks; third, the identity oflocal citizenship - sense of belonging, solidarity and equality with members of community groups;fourth, the principle of reciprocity and the value of cooperation or collaboration, the sense of dutyto help others and self confidence when accompanying, and; fifth, trust in the community. The type of this study is ethnographic research, that is research that tries to find out, toreveal and to explain cultural behavior of society or community in certain place in detail anddepth. This study uses macth method approach, namely approach method which combinesqualitative and quantitative data. The excavation of qualitative data is done by inclusionobservation and in-depth interview on the informant while the quantitative data is obtained byspreading questionaires on respondent and recording as well as literature study. This researchapproach model is intended to explore qualitative data supported by quantitative data so it enablesto get in depth and detail description of the resilience of coastal women to HIV / AIDS based onsocial capital. This study will be carried out for two years. The first year of research will identifyand map the local social potential of coastal communities in the south of Jember regency. Thesecond year of research activity formulate how the potential of the social capital can be used asmedia of resilience in preventing the spread of HIV / AIDS among coastal women who are said tobe vulnerable groups.Keywords: model, coastal women, HIV/ AIDS, social capital, local